The Solar and Geomagnetic Storms in 2024 May: A Flash Data Report - Hisashi Hayakawa; Yusuke Ebihara; Alexander Mishev; Sergey Koldobskiy; Kanya Kusano; Sabrina Bechet; Seiji Yashiro; Kazumasa Iwai; Atsuki Shinbori; Kalevi Mursula; Fusa Miyake; Daikou Shiota; et al. (The Astrophysical Journal)
In 2024 May, the scientific community observed intense solar eruptions that resulted in a great geomagnetic storm and auroral extensions, highlighting the need to document and quantify these events. This study mainly focuses on their quantification. The source active region (AR; NOAA Active Region 13664) evolved from 113 to 2761 millionths of the solar hemisphere between May 4 and 14. NOAA AR 13664’s magnetic free energy surpassed 10 ^33 erg on May 7, triggering 12 X-class flares on May 8–15. Multiple interplanetary coronal mass ejections (ICMEs) were produced from this AR, accelerating solar energetic particles toward Earth. According to satellite and interplanetary scintillation data, at least four ICMEs erupted from AR 13664, eventually overcoming and combining each other. The shock arrival at 17:05 UT on May 10 significantly compressed the magnetosphere down to ≈5.04 R _E and triggered a deep Forbush Decrease. GOES satellite data and ground-based neutron monitors confirmed a ground-level enhancement from 2 UT to 10 UT on 2024 May 11. The ICMEs induced exceptional geomagnetic storms, peaking at a provisional Dst index of −412 nT at 2 UT on May 11, marking the sixth-largest storm since 1957. The AE and AL indices showed great auroral extensions that located the AE/AL stations into the polar cap. We gathered auroral records at that time and reconstructed the equatorward boundary of the visual auroral oval to 29.°8 invariant latitude. We compared naked-eye and camera auroral visibility, providing critical caveats on their difference. We also confirmed global disturbances of the storm-enhanced density of the ionosphere.